The Efficacy of Bleeding Acupuncture Point UB-40 in Patients Suffering from Severe Acute Lumbago : Efficacy of Bleeding Acupuncture Point UB-40 - Hassan, Muhammad Waseem; Anwar, Shahzad; Shaukat, Gull a Rukh; Ali, Zulfiqar (Pakistan Journal of Health Sciences, 2023)
Severe acute lumbago, or lower back pain, is a common condition that can cause sudden pain and cramping that lasts for days to weeks. The UB-40 acupuncture point, also known as the Urinary Bladder 40, is a sensitive point that provides excellent relief from spinal pain. Objective: To evaluate the efficacy of bleeding acupuncture point UB-40 in patients suffering from severe acute lumbago. Methods: An experimental pre-post study was conducted on 40 participants, recruited from the emergency department (ED) of Iffat Anwar Medical Complex Lahore from January 2021 to February 2023. All the patients were treated with bleeding at UB-40 acupuncture point technique. After the treatment, the patients were followed at baseline, 1-week and 1-month intervals. The primary outcomes of the study were to determine the improvement in acute low back pain by using the visual analogue scale (VAS) and physical impairment using Oswestry low back disability index (ODI) scale. Results: A total of 40 patients were enrolled in the current study. The mean age of patients was 38.7±12.2. Majority of the patients were females (52%). The mean pain score (VAS) at baseline was 8.00±0.751, which reduced at 4th week with a mean pain score of 2.92±1.28. Moreover, at baseline, patients had severe disability with a mean ODI score of 55.58, but after treatment it gradually decreased to (25.55). Conclusions: It was concluded that acupuncture, especially with bleeding at UB-40 point, may provide an immediate significant effect in reducing the acute pain of low back and disability.